The influence of nanoparticles and their functionalization on the dielectric properties of biaxially oriented polypropylene for power capacitors - Streibl, Maximilian; Werner, Siegfried; Kaschta, Joachim; Schubert, Dirk W.; Moos, Ralf (IEEE Transactions on Dielectrics and Electrical Insulation, 2020)
In this work, eleven commercially available nanoparticles are benchmarked against each other according to their potential for an application in a polypropylene (PP) based nanocomposite for thin film power capacitors. Biaxially oriented films containing a fixed concentration of 5 wt%. Al2O3, TiO2, SiO2, or POSS nanoparticles with different surface functionalization were analyzed by dielectric spectroscopy and dielectric breakdown measurements. Two particle systems emerged to increase both the dielectric breakdown strength and the reliability of the films combined with low dielectric losses. The effects of the particles were in agreement with the multicore model of Tanaka et al. The particle dispersion was analyzed on SEM images. A correlation between agglomerates and zeta potential in isopropanol was found yielding a quick analysis tool for the tendency of nanoparticles to form clusters during processing with PP. To assure comparability between the films, the real particle content was determined by incineration. The surface roughness of the film has a large influence on the breakdown behavior and was, therefore, also monitored.
CRIS-Team Scopus Importer:2020-04-14
Keywords: dielectric breakdown; dielectric films; dielectric losses; dielectric materials; nanocomposites